Discourses of loss of professional status and gender discrimination among migrant physicians in Chile - Lazzaro-Salazar, Mariana (Círculo de Lingüística Aplicada a la Comunicación, 2025)
Cultural transitions are sites of identity struggle since professionals often need to revise their disciplinary values and ideologies, their professional identity stance and claims and their professional practices in the light of the beliefs and expectations of their peers in the host culture. Drawing on data from sociolinguistic interviews, this study explores the role and discursive construction of professional identity in discourses of status loss and gender discrimination of migrant physicians (mainly of Latin-American origin) who have faced challenges that not only damaged their professional image but also constrained their ability to practice medicine during their cultural transition in public hospitals in Chile. Adopting an interactional sociolinguistic perspective, the study discusses how related disempowering actions may affect migrant physicians’ self-esteem and how some employ their professional identity as a resource to cope whenever their integrity as people and as professionals is threatened by local physicians’ discriminatory behaviour and/or their loss of professional status.